(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The rapid expansion of digital technologies has fundamentally transformed research, teaching, and knowledge production globally, leading to the emergence of Digital Humanities (DH) as a dynamic interdisciplinary field. Despite this global shift, the integration of DH within African Open and Distance Learning (ODL) institutions remains underexplored and under-theorized. This study investigated the institutional and pedagogical viability of integrating Digital Humanities programmes in Nigerian ODL universities, with particular reference to the National Open University of Nigeria. Adopting a mixed-methods research design, the study drew on data collected from 200 respondents, including academic staff, postgraduate students, and ICT personnel. Quantitative data were analysed using both descriptive and inferential statistics, including Pearson correlation and multiple regression analyses, while qualitative data were subjected to thematic analysis. Reliability testing yielded Cronbach’s alpha coefficients ranging from 0.76 to 0.84, with an overall reliability index of 0.82, indicating strong internal consistency. The findings revealed a moderate level of institutional readiness for DH integration, accompanied by significant infrastructural, pedagogical, and policy-related constraints. Inferential analysis shows that digital infrastructure is the strongest predictor of pedagogical viability (β = 0.41, p < 0.001), followed by faculty competence (β = 0.35) and curriculum adaptability (β = 0.29). Qualitative insights further highlight challenges related to funding, digital literacy gaps, and the absence of structured policy frameworks. The study contributes to scholarship by proposing a context-sensitive, multidimensional model of DH integration in ODL systems, and by extending the application of Connectivism, TPACK, and Diffusion of Innovation theories within developing educational contexts. It also advances ongoing efforts to decolonize Digital Humanities by foregrounding African institutional realities. The study concludes that while DH integration in Nigerian ODL universities is both viable and strategically necessary, its success depends on coordinated investments in infrastructure, faculty development, curriculum innovation, and policy support.